(untitled) (World Bulletin of Social Sciences, 2023)
The current research aims at measuring the impact of marketing excellence represented in (marketing creativity, essential capabilities, appropriate price, and continuous improvement) on engaging in the insurance service represented by (availability, cooperation, seeking assistance, and commitment to rules). It also aims at measuring the study problem represented in the impact of marketing excellence on engaging in the insurance service at the National Insurance Company. (125) questionnaire forms were distributed, (80) questionnaire forms were distributed, and (71) were retrieved, (3) of them were damaged. This means that the number of questionnaires valid for analysis is (68). In order to extract the desired results, the research used a set of important statistical methods. These methods are normal distribution, Cronbach’s alpha stability coefficient, arithmetic mean, standard deviation, and structural equation modeling. The research summarized a set of important results, perhaps the most prominent of which is that improving marketing excellence at the National Insurance Company contributes in encouraging workers to engage in the insurance service.